COVID-19: A challenge for forensic and pathological researchers - Huang Sizhe; Wang Rongshuai; Wang Yunyun; Zhang Junchao; Zhang Youyou; Guan Chuhuai; Zhang Jie; Yu Yalei; Tian Qishuo; Qu Guoqiang; Liu Qian; Zhou Yiwu; et al. (Wolters Kluwer Medknow Publications, 2020)
Coronavirus disease 2019 (COVID-19) emerged in Wuhan, Hubei province, in December 2019, then spread rapidly in a very short time resulting in thousands of deaths. Unfortunately, details about the pathological mechanisms involved in the disease - including those associated with death - are currently scant. It is important to perform autopsies and pathological examinations of patients who have died from COVID-19 as soon as possible. This is the responsibility of forensic and pathological researchers, but it does pose various challenges. Such autopsies should be conducted in an isolated operating room under constantly maintained negative pressure. The examiners should be protectively equipped in accordance with biosafety level 3 requirements. It is essential to disinfect the room, facilities, instruments, and materials after the procedure and to dispose of all wastes appropriately. Cautious and precise operations during autopsies and pathological examinations will minimize the possibility of viral transmission. As many autopsies of COVID-19 patients as possible should be performed, until a detailed understanding of the mechanisms involved in COVID-19 pathogenesis and death has been attained.